ANALISIS DESKRIPTIF PENERAPAN MODEL PEMBELAJARAN BCCT DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS PADA ANAK USIA DINI - Uswatun Uswatun; Lilis Suryani; Mona El Liza; Nor Ilman Saputra (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This study aims to describe the development of children's critical thinking skills (cognitive) in learning the BCCT model. Because the ability to think critically (cognitive) is an important aspect of child development that is directly related to the learning process and determines the success of children in school. The focus of this research is to determine the background, objectives, plans, concepts, benefits, advantages, disadvantages, and the impact of the BCCT learning model in developing children's critical thinking skills. The research approach used is a qualitative approach and uses a type of descriptive research that attempts to describe and interpret existing data. Data collection techniques in this study used the Miels and Hubeman model of analysis, namely observation, interviews, and documentation. Data analysis through data collection, data reduction, data presentation and drawing conclusions. The results of the research conducted by the researcher can be concluded that: the application of BCCT learning in developing critical thinking skills children are very enthusiastic in every game play, which is carried out using four playing platforms, namely: environmental footholds, initial footings, playing platforms, playing platforms, footing after playing. Playing activities at the children's center can stimulate the development of critical (cognitive) thinking skills. Thus researchers can conclude that learning BCCT can improve children's critical thinking skills.